Mid-level managers’ perspectives on implementing isoniazid preventive therapy for people living with HIV in Ugandan health districts: a qualitative study - Christian, Canice; Kakande, Elijah; Nahurira, Violah; Akatukwasa, Cecilia; Atwine, Fredrick; Bakanoma, Robert; Itiakorit, Harriet; Owaraganise, Asiphas; DiIeso, William; Rast, Derek; Kabami, Jane; Peretz, Jason Johnson; et al. (BioMed Central Ltd, 2024)
Abstract Background Isoniazid preventive therapy (IPT) works to prevent tuberculosis (TB) among people living with HIV (PLHIV), but uptake remains low in Sub-Saharan Africa. In this analysis, we sought to identify barriers mid-level managers face in scaling IPT in Uganda and the mechanisms by which the SEARCH-IPT trial intervention influenced their abilities to increase IPT uptake. Methods The SEARCH-IPT study was a cluster randomized trial conducted from 2017-2021. The SEARCH-IPT intervention created collaborative groups of district health managers, facilitated by local HIV and TB experts, and provided leadership and management training over 3-years to increase IPT uptake in Uganda. In this qualitative study we analyzed transcripts of annual Focus Group Discussions and Key Informant Interviews, from a subset of SEARCH-IPT participants from intervention and control groups, and participant observation field notes. We conducted the analysis using inductive and deductive coding (with a priori codes and those derived from analysis) and a framework approach for data synthesis. Results When discussing factors that enabled positive outcomes, intervention managers described feeling ownership over interventions, supported by the leadership and management training they received in the SEARCH-IPT study, and the importance of collaboration between districts facilitated by the intervention. In contrast, when discussing factors that impeded their ability to make changes, intervention and control managers described external funders setting agendas, lack of collaboration in meetings that operated with more of a 'top-down' approach, inadequate supplies and staffing, and lack of motivation among frontline providers. Intervention group managers mentioned redistribution of available stock within districts as well as between districts, reflecting efforts of the SEARCH-IPT intervention to promote between-district collaboration, whereas control group managers mentioned redistribution within their districts to maximize the use of available IPT stock. Conclusions In Uganda, mid-level managers' perceptions of barriers to scaling IPT included limited power to set agendas and control over funding, inadequate resources, lack of motivation of frontline providers, and lack of political prioritization. We found that the SEARCH-IPT intervention supported managers to design and implement strategies to improve IPT uptake and collaborate between districts. This may have contributed to the overall intervention effect in increasing the uptake of IPT among PLHIV compared to standard practice. Trial registration ClinicalTrials.gov, NCT03315962, Registered 20 October 2017. Keywords: TB preventive therapy, Mid-level managers, Health systems
Keywords: TB preventive therapy, Mid-level managers, Health systems